(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Menopause is associated with adverse changes in lipid profiles and cardiometabolic risk factors, yet comprehensive hospital-based data from Bangladesh remain scarce. We evaluated the prevalence of dyslipidemia, metabolic syndrome, hypertension, diabetes, and physical inactivity and their association with menopausal status in Bangladeshi women attending a tertiary care hospital. Methods: In this cross-sectional study, 408 women aged 30–65 years were enrolled consecutively from the cardiology outpatient department of Bangabandhu Sheikh Mujib Medical University, Dhaka (January–December 2022). Menopausal status was the primary exposure. Dyslipidemia was defined by ATP-III criteria (TC≥200 mg/dL, TG≥150, LDL≥130, or HDL<40 mg/dL). Metabolic syndrome was defined as ≥3 of NCEP/IDF criteria. We compared outcomes by menopausal status and used logistic regression (multivariable and propensity-score–adjusted) to estimate odds ratios (OR) and 95% confidence intervals (CI). Results: Of 408 women (mean age 46.2±9.4 years), 204 (50.0%) were postmenopausal. Postmenopausal women had significantly higher prevalence of dyslipidemia (98.0% vs. 33.8%, p<0.001), metabolic syndrome (98.0% vs. 13.7%, p<0.001), hypertension (92.6% vs. 3.4%, p<0.001), diabetes (46.1% vs. 0.5%, p<0.001), and physical inactivity (84.3% vs. 60.3%, p<0.001). Mean systolic blood pressure was 24 mmHg higher in postmenopausal women (156±12 vs. 132±11 mmHg, p<0.001). In crude analysis, menopause was strongly associated with dyslipidemia (OR 97.8, 95% CI 34.9–274.4) and metabolic syndrome (OR 314.3, 95% CI 108.1–913.6). After adjusting for age, BMI, diabetes, and hypertension, menopause remained significantly associated (adjusted OR for dyslipidemia 81.3, 95% CI 16.2–408.5; for MetS 255.4, 95% CI 40.5–1610.2). Propensity-score matched results were consistent. Conclusions: Postmenopausal status was strongly associated with markedly elevated prevalence of dyslipidemia, metabolic syndrome, hypertension, diabetes, and physical inactivity in this tertiary hospital cohort, with near-universal dyslipidemia (98%) and metabolic syndrome (98%) in postmenopausal women. The high prevalence reflects the tertiary care setting (referral bias toward higher-risk patients) and indicates urgent need for menopause-sensitive cardiometabolic screening protocols in hospital-based populations. Prospective studies are needed to establish temporal causality and evaluate prevention strategies. Journal of Paediatric Surgeons of Bangladesh (2024) Vol. 15 (1 & 2): 23-28